Pengaruh Kegunaan, Persepsi Kemudahan, Persepsi Kenyamanan, Persepsi Resiko, Dan Kepercayaan Terhadap Minat Menggunakan Internet Banking (Studi kasus pada Bank BRI Unit Salatiga) - Hidayatullah, Satria Hatma; , Dr. Fatchan Achyani, M.Si (2017)
This study aims to investigate the influence of usefulness, perceived ease, comfort perception, risk and trust in the interest of the use of Internet Banking. Data consisted of 100 respondents were selected using the method of accidental sampling. This study shows that the usefulness, perceived ease, comfort perception, the perception of risk and trust affect the desirability of using Internet Banking. The relationship between usefulness, perceived ease, comfort perception, the perception of risk and trust affect the interest of the use of Internet Banking.